Field notes contributed by James J. Dinsmore, spring 1997 - Dinsmore, James J.et al (1997)
List of birds and locations contributed by James J. Dinsmore with observers Jane Schuster, Steve E. Fairbairn, Ron Sarno and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1997. Epson - sheet feed